Mais PAIC: avaliação da política de formação docente continuada na perspectiva de docentes em uma escola da rede municipal de Fortaleza/CE - Oliveira, Virginia Moura Garcia (2022)
Bearing in mind the inefficient context of the educational system in Ceará, evidenced in 2004 based on the work carried out by the Ceará Committee for the Elimination of School Illiteracy - CCEAE, a collaboration pact was signed between the state and municipalities in the fight against illiteracy in children in the early years of elementary school. The Literacy Program at the Right Age, established by Law No. 14026/2007, was implemented in the state of Ceará in 2007 and expanded in 2015 to MAIS PAIC. Based on the actions implemented by the program, the objective of this study is to evaluate the contributions of the continued teacher training policy at MAIS PAIC, considering the perspective of literacy teachers at the João Saraiva Leão School of the public education network in Fortaleza. This is a research focused on a qualitative, exploratory approach, choosing the case study method. Data collection was developed from documental analysis of records and results about the program and semi-structured interviews with literacy teachers and school managers (pedagogical management and coordination). The investigation is based on the perspective of in-depth evaluation, proposed by Rodrigues (2008), which seeks beyond the study of official documents and quantitative results, the understanding of the meanings of the policy for the actors who experienced it. Throughout the study, it became evident that the program is based on the policy of accountability and management for results, in addition to being based on the principle of cooperation between state and municipalities. In this context, the results indicate that the MAIS PAIC actions contributed to the constitution of the teacher's personal and professional identity in aspects such as reflection on practice, exchange of experiences, and this reflected in student learning. program aspects that contributed to teacher training, it is observed that there are still elements that configure a vertical perspective and a public policy format that collaborates to update knowledge.